Analisis Pengaruh Kinerja Keuangan, Growth Opportunity Dan Ukuran Perusahaan Terhadap Struktur Modal Dan Nilai Perusahaan - Irrofatun Kusna; Erna Setijani (University of Merdeka Malang, 2018)
This research aims to analyze the influence of liquidity, profitability, growth opportunity, company size and capital structure to company value. The population of this research is food and beverage companies listed in Indonesian Stock Exchange period 2012 – 2016. The technique used in sampling is purposive sampling. The sample in this study is nine companies. Data analysis using SmartPLS. The result of this study shows that growth opportunity and company size have positive and significant influence to company value. Profitability and capital structure have negative and significant influence to company value. Liquidity has positive and not significant influence to company value. Liquidity and profitability have negative and significant influence to capital structure. Growth opportunity and company size have positive and not significant influence to capital structure. Capital structure as an intervening variable from liquidity and profitability to company value, but not for growth opportunity and company size to company value. https://doi.org/10.26905/jmdk.v6i1.2155